Drug demand reduction needs assessment in the Caribbean Community and Market - Klein, Axel...[et al] (DrugScope LondonGB, 2002)
Outlines key challenges facing the Caribbean Community in reducing the demand for drugs. Identifies the principal areas where demand reduction activities may be further developed and enhanced.